Emir Abdülkadir el-Cezâirî’nin velâyet anlayışı - (:unkn) unknown (My University, 2012)
Bu makalede Emir Abdülkadir el-Cezâirî’nin tasavvufun temel konularından velâyet meselesine bakışı, ilgili nasları yorumlama şekli, velâyetin nübüvvet, vahiy ve Kur’an’la alâkası, evliyânın tabaka ve mertebeleri, Hızır’ın peygamber mi velî mi olduğu, velâyetin vehbîliği gibi konulardaki görüşleri ortaya konmuştur. Velâyet konusu çerçevesinde Abdülkadir el-Cezâirî’nin dayandığı kaynaklar ve şahsiyetler ile tasavvuf kültürüne hâkimiyeti tespit edilmeye çalışılmıştır.

This article will present Amir Abd al-Qādir al-Jazā’iri’s views on sainthood, which is one of the basic subjects of Sufism, the way of his interpretations of the verses related to the subject, what his opinion was about the relationship of sainthood (walaya) to prophethood (nubuwwa) and the Qur’an, levels and degrees of saints, whether Khidr was a saint or a prophet, and his views on divine origins of sainthood. In this article we have also tried to determine al-Jazā’iri’s mastery over the Sufi tradition within the context of the subject of sainthood based on his sources of information
Amir Abdulqadir al-Jazâirî’s views on sainthood (Walayah)
Keywords: Din Bilimi